2020
DOI: 10.2478/rjim-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of severity of acute pancreatitis over time

Abstract: AbstractIn recent years there has been an increase in the incidence of acute pancreatitis worldwide. In spite of efforts to improve the treatment and care of patients with acute pancreatitis, to develop imaging investigations and interventional diagnostic and treatment techniques and to facilitate patients’ access to them, acute pancreatitis continues to be associated with significant mortality and morbidity, and the treatment of patients suffering from this disease entails sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…Moreover, the genetic aspect seems to be correlated with chronic pancreatitis [ 54 ], an important risk factor for PC [ 55 ], leading to endocrine and exocrine dysfunction [ 56 ]. Pancreatitis pathology is characterized by malabsorption, steatorrhea, fat-soluble vitamin deficiency, osteoporosis, and diabetes [ 56 , 57 ]. Patients diagnosed with chronic pancreatitis have a 14-fold risk of developing PC [ 58 ].…”
Section: Pancreatic Cancer Risk Factorsmentioning
confidence: 99%
“…Moreover, the genetic aspect seems to be correlated with chronic pancreatitis [ 54 ], an important risk factor for PC [ 55 ], leading to endocrine and exocrine dysfunction [ 56 ]. Pancreatitis pathology is characterized by malabsorption, steatorrhea, fat-soluble vitamin deficiency, osteoporosis, and diabetes [ 56 , 57 ]. Patients diagnosed with chronic pancreatitis have a 14-fold risk of developing PC [ 58 ].…”
Section: Pancreatic Cancer Risk Factorsmentioning
confidence: 99%
“…[23] SAPS-II is an alternative version of the APACHE scale that is frequently used in the ICU setting. [24] Notably, SAPS-II is a predictor of mortality in patients with AP. [25] As such, all five of the predictors incorporated into our developed nomogram represent credible mortality-related risk factors worthy of consideration in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…It was recommended that nasojejunal route could be selected for nutritional support for patients after surgical intervention. Another study (26) showed that SAP patients with early enteral feeding (usually in 24h after admission) would reducing the rate of infection or death, which is another intervention demonstrated to be clinical benefit in the management of patients with pancreatitis Over the years there are many classifications and scores to diagnose and assess the severity of the SAP such as the APACHE Score, and the Ranson score, (27). Temporarily there are no directly pharmacotherapy for treating with SAP, strategies are targeted at preventing end-organ damage or reducing complications (28).…”
Section: Discussionmentioning
confidence: 99%